Community Services for the Children of Migrant Labors through Informal Education to Support SDGS in Hulu Kelang Selangor Learning Places - Nadiah Awary; Tony Seno Aji; Mohammad Wasil; Lady Wajuba Perdini Fisabilillah; Nurul Hanifa; Ruth Eviana Hutabarat; Wenny Restikasari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
An analysis of the education situation in Indonesia, focusing on the impact of the unequal education structure on the economic sector and the high poverty rate. These problems have led to an increase in the number of Indonesian migrant workers (PMI) in Malaysia, including their children who face obstacles in obtaining formal education. This report describes the Government of Indonesia's initiative through the Indonesian Embassy in Malaysia to establish non-formal schools, such as Sekolah Indonesia Kuala Lumpur (SIKL) and Sanggar Bimbingan Hulu Kelang, as an alternative to providing access to education to immigrant children. However, legal issues related to the citizenship of immigrant children complicate the government's efforts to provide protection and proper education. The focus of the report also reveals a lack of public literacy regarding the procedures for working abroad, affecting the validity of immigrants' documents and their children's education rights. Mentorship centers, such as Sanggar Bimbingan Hulu Kelang, are emerging as a solution in helping immigrant children obtain basic education and overcome administrative barriers. Collaboration between the Government of Indonesia, universities and communities through Kuliah Kerja Nyata (KKN) activities in Malaysia is a positive step in addressing community education and literacy issues. The report also details the collaboration between INTI and the rectors' assembly and the role of students in making a positive impact. Despite the obstacles, the success of the KKN program proves that active community participation can make a difference in improving the quality of education among Indonesian immigrants in Malaysia.